The Efficacy of Self-Paced Video Lessons on the Performance of Grade 7 Students in Mathematics - Love Harzil L. Abugho; Elizabeth L. Baguio (Randwick International of Education and Linguistics Science Journal, 2026)
This study investigated the effectiveness of self-paced video lessons delivered through Khan Academy in improving the Mathematics achievement of Grade 7 students at Lunao National High School, Division of Gingoog City, during the 2025–2026 academic year. The research utilized a quasi-experimental pretest–posttest control group design involving seventy Grade 7 learners who were assigned to either a control group or an experimental group through matched-pair random sampling based on their Mathematics Mean Percentage Scores (MPS). Students in the control group received conventional classroom instruction, whereas those in the experimental group participated in a blended learning approach incorporating Khan Academy self-paced video lessons for five weeks. A researcher-adapted 50-item multiple-choice examination aligned with the MATATAG curriculum served as the primary data-gathering instrument. Descriptive statistics, including mean and standard deviation, together with t-test analysis, were employed to evaluate the data. Results indicated that both groups demonstrated improvement after the intervention; however, the experimental group achieved significantly greater learning gains than the control group. Statistical analysis yielded a t-value of 3.671 and a p-value below .001, confirming a significant difference between the two groups in favor of the experimental condition. The findings suggest that integrating self-paced video lessons through Khan Academy is more effective than traditional teaching methods in enhancing Grade 7 students’ Mathematics performance. Consequently, the study recommends the incorporation of Khan Academy as a supplementary instructional resource to support student achievement, engagement, and learning outcomes in Mathematics.